PENGARUH BUDAYA ORGANISASI TERHADAP SIKAP PERUBAHAN ORGANISASI DENGAN COMMITMENT ORGANISASI SEBAGAI VARIABEL MODERASI (STUDI KASUS PADA APARATUR SIPIL NEGARA (ASN) KATOR KECAMATAN SE KOTA PARIAMAN - Yulihardi, Yulihardi (Eko dan Bisnis: Riau Economic and Business Review, 2019)
Problem analysed in this research is " Organizational Change Attitude of Aparatur of State Civil ( ASN) of As for this research variable is Organizational Cultural influence, and Organizational Commitment (as free variable) and Organizational Change Attitude of Aparatur of State Civil (ASN) ( as variable trussed). This research pay attention to the Organizational Change Attitude storey;level of Aparatur of State Civil (ASN) as well as require to be paid attention to by a Organizational Culture, and the Organizational Commitment. By striving to improve the Organizational Change Attitude of Aparatur of State Civil (ASN) in order to attainment of Institution target, specially to Office of Subdistrict of Pariaman Town. This elite aim to to lay open the, Organizational Cultural Influence to Organizational Change Attitude of Aparatur of State Civil (ASN) By Commitment is Organizational as moderator variable of at Office of Subdistrict of Pariaman Town. showing signifikansi band usher the variable in structural model seen from statistical t usher the variable. Each; Every independent variable of examinee in structural model of] this research not all own the influence signifikan to this variable dependennya. Is proven from value T-Statistics which not all bigger than 1.96 ( examination two-tailed = 0,05). [Relation/Link] test usher the variable indicate that the organizational culture to positive Organizational Change Attitude ( 0,279) and signifikan at = 0,05 with the value statistic 3,592 > 1,96, inferential so that that supported first hypothesis. organizational culture to Organizational Commitment and got [by] a positive result ( 0,472) and signifikan of = 0,05 with the value statistic 0,348 < 1,96, Inferential so that that second hypothesis is not supported. Organizational variable Commitment influence to positive Organizational Change Attitude (0,367) and signifikan of = 0,05 with the value statistic 2,052 > 1,96. Inferential so that that hypothesis is third supported. organizational culture to Organizational Change Attitude [through/ passing] got by organizational Commitment of positive result ( 0,351) and signifikan = 0,05 with the value statistic 2,317 > 1,96, inferential so that that supported fourth hypothesis. Conclusion from research that Organizational Cultural variable Hypothesis, and proven to Organizational Commitment own the positive influence and signifikan to Organizational Change Attitude At Aparatur of State Civil (ASN) of either through direct and also indirectly Office of Subdistrict of Pariaman Town by Average is adjusted R-Squared ( AARS)=0.399, P<0.001 Contribution 39,9%. Suggestion to be more focus to improve;repair the variable, by paying attention to its indicators